2015
DOI: 10.3366/cor.2015.0072
|View full text |Cite
|
Sign up to set email alerts
|

A corpus-assisted study of the discourse markerwellas an indicator of judges' institutional roles in court cases with litigants in person

Abstract: The article concentrates on court cases with litigants in person (lay people who act on their own behalf in legal proceedings without a counsel or solicitor) and discusses the challenges of building a corpus of courtroom discourse where it is crucial to distinguish between speakers due to their distinct institutional roles. The corpus incorporates seven sub-corpora of verbatim transcripts from different court cases with litigants in person and comprises over 11 million tokens. The focus of the article is on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…A meta-analysis by Nartey and Mwinlaaru (2019) has shown that corpus-assisted approaches are frequently used in linguistics, and yet they identify a lack of such research "in the allied field of critical genre analysis and forensic contexts as well (as) those of contrastive/intercultural rhetoric, narrative inquiry/analysis, mediated discourse analysis, and conversation analysis have hardly been engaged" (p. 19, my emphasis). Thus, the present paper aims at contributing to the extant literature in the area of corpus-assisted discourse analysis in forensic contexts (e.g., Coulthard, 1994;Kredens, 2002;Cotterill, 2003;Heffer, 2005;Gruber, 2014;Felton Rosulek, 2015;Gales, 2015;Tkacuková, 2015;Wright, 2021), and it is also the first one, to my knowledge, to address the language of private prison corporations in the United States.…”
Section: Data Methodology and Research Questionsmentioning
confidence: 99%
“…A meta-analysis by Nartey and Mwinlaaru (2019) has shown that corpus-assisted approaches are frequently used in linguistics, and yet they identify a lack of such research "in the allied field of critical genre analysis and forensic contexts as well (as) those of contrastive/intercultural rhetoric, narrative inquiry/analysis, mediated discourse analysis, and conversation analysis have hardly been engaged" (p. 19, my emphasis). Thus, the present paper aims at contributing to the extant literature in the area of corpus-assisted discourse analysis in forensic contexts (e.g., Coulthard, 1994;Kredens, 2002;Cotterill, 2003;Heffer, 2005;Gruber, 2014;Felton Rosulek, 2015;Gales, 2015;Tkacuková, 2015;Wright, 2021), and it is also the first one, to my knowledge, to address the language of private prison corporations in the United States.…”
Section: Data Methodology and Research Questionsmentioning
confidence: 99%
“…In recent years, there has been an increasing interest among linguists to use a corpus-based approach (e.g. Cotterill, 2003;Archer, 2005;Heffer, 2005;Johnson, 2014Johnson, , 2015Tkačuková, 2015) for the macro and micro analysis of courtroom interaction. Despite this encouraging phenomenon, there has been very little quantitative work conducted on questions in courtroom interaction, due to the methodological challenges, such as inaccessibility of sufficiently large amounts of data and technology (e.g.…”
Section: Justifying the Current Studymentioning
confidence: 99%
“…On the micro level, various studies look at the illocutionary force (Cotterill, 2003), discourse markers (Hale, 1999;Tkačuková, 2015) and metalinguistic markers (Heffer, 2005) that accompany questions. Although these markers may or may not carry "propositional content" (Hale, 1999: 59), they are important to express a speaker's intention in their utterance.…”
Section: Questioning In Legal Settings and In The Courtroommentioning
confidence: 99%
“…Research directly dealing with linguistic aspects of litigation in person is limited to two short studies on small claims courts (O'Barr and Conley, 1990;Conley and O'Barr, 1998) and research conducted by the author (Tkacukova, 2010(Tkacukova, , 2011(Tkacukova, , 2015. The first two studies deal with narrative devices used by self-represented litigants in the USA and conclude that lay people present narratives common in everyday conversations and therefore produce relational accounts instead of rule-oriented accounts required for the purposes of courts (e.g.…”
Section: Linguistic Research On Self-representationmentioning
confidence: 99%
“…This influences the role of judges who often have to explain common legal concepts, such as 'evidence', 'opening speech', or 'cross-examination' to lay people. In Tkacukova (2015), the most frequent function judges performed when talking to LiPs was to provide explanation or suggestions on procedural matters and legal concepts. Difficulties faced by lay people inadvertently complicate the role of the court staff, the other parties' legal representatives and judges.…”
Section: On Cross-examination Conducted Bymentioning
confidence: 99%